Comparative Analysis of Company Financial Performance Before and After Acquisition - Izza, Alfiano; Djazuli, Atim (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2025)
Purpose – This study aims to compare the financial performance of companies before and after acquisitions by analyzing selected firms listed on the Indonesia Stock Exchange. Design/methodology/approach – This study employs a quantitative comparative research design using secondary financial statement data from five companies listed on the Indonesia Stock Exchange: PT Astra Otoparts Tbk, PT Bayan Resources Tbk, PT Indospring Tbk, PT MNC Land Tbk, and PT Telekomunikasi Indonesia Tbk. Financial performance was evaluated over a five-year period before the acquisition (2008–2012) and a five-year period after the acquisition (2014–2018) using the Current Ratio (CR), Debt-to-Equity Ratio (DER), Total Asset Turnover (TATO), Return on Assets (ROA), Return on Equity (ROE), Net Profit Margin (NPM), and Earnings per Share (EPS). The data were analyzed using the Kolmogorov–Smirnov normality test, paired-sample t-test, and Wilcoxon signed-rank test. Findings – The findings indicate significant differences in several financial performance indicators between the pre-acquisition and post-acquisition periods. Earnings per Share (EPS) decreased significantly following the acquisitions, while Return on Assets (ROA) and Total Asset Turnover (TATO) did not exhibit significant differences. Overall, the results suggest that acquisitions have mixed effects on corporate financial performance, generating both positive and negative changes across different financial indicators. Originality/value – This study contributes to the understanding of acquisition outcomes in emerging markets by providing empirical evidence on post-acquisition financial performance in Indonesia. The findings offer practical insights for investors and corporate managers in assessing the effectiveness of acquisition strategies and their implications for long-term financial sustainability.